Strong copyright + DRM + weak net neutrality = digital dystopia? - Bailey CW Jr. (Information Technology & Libraries, 2006)
Three critical issues--a dramatic expansion of the scope, duration, and punitive nature of copyright laws; the ability of Digital Rights Management (DRM) systems to lock-down digital content in an unprecedented fashion; and the erosion of Net neutrality, which ensures that all Internet traffic is treated equally--are examined in detail and their potential impact on libraries is assessed. How legislatures, the courts, and the commercial marketplace treat these issues will strongly influence the future of digital information for good or ill.